JURISDICTIONAL FEATURES OF INQUIRY IN CASES OF POLITICAL CRIMES IN THE RUSSIAN EMPIRE (1864-1904) - Les, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the study is to analyze the jurisdiction of the inquiry bodies to investigate political crimes in the russian empire (1864-1904). The achievement of this goal is ensured through the search for scientific and theoretical constructions on specific historical and legal material. Results: the main jurisdictional features of the bodies of inquiry in cases of political crimes in the russian empire (1864-1904) were revealed. In our opinion, the materials of the article can be used in preparation of new courses in the theory and history of state and law, which are taught in higher education institutions of Ukraine, mainly when studying the formation and development of the system of pre-trial investigation bodies of Ukraine. Discussion of the results is that the article attempts to identify and analyze the problem of jurisdiction over the inquiry function between the prosecutor's office and the Special Corps of Gendarmes for political crimes in the russian empire after the judicial reform in 1864. The conclusions proposed by the author are important for the further development of inquiry and investigation bodies and in-depth scientific research of legal issues, practical implementation of these historical achievements in reforming state law enforcement agencies authorized to conduct pre-trial investigations. Research materials can be used in the direct practical activities of law enforcement officials, scholars of the history of law and law students. In addition to the scientific significance, as well as the possibilities of application in the educational process of this article, it should be noted its relevance to the legislative and legislative process. The practical significance of the article is that it is a contribution to the formation of scientific historical and theoretical concepts about the structure and activities of certain law enforcement agencies of the russian empire in the pre-revolutionary period.